Perancangan Model Bisnis Kuma Suki Menggunakan Bisnis Model Kanvas - Putri Berlianti; Imanuddin Hasbi (Cakrawala Repositori IMWI, 2019)
The growing variety of culinary business in Indonesia, especially foreign food, makes the business continues to create innovation and creativity, one of which is Kuma Suki. By researching Kuma Suki, researchers took the initiative to solve problems and provide solutions for Kuma Suki to be better.This study aims to identify, make SWOT analysis, and map business processes Kuma Suki using nine elements of the business model canvas that can solve problems. The research method used is qualitative with descriptive research design. Data collection methods used are primary data collection methods with data collection techniques interviews, observation, documentation and triangulation. The results showed that the business model needs improvement of value proposition by adding flavor variant, menu innovation every month, and welcome drink. Customer segments by serving catering to add consumers in the office environment and parties. Channel to have a website for consumers to make reservations easily. Customer relationships in order to hold a promo, follow the culinary event, provide souvenirs and provide a membership system. Key activities to control the product. Key resources to expand the stock of raw materials and decoration. Key partnerships to partner with labeling companies and ICA. Revenue stream to open franchise.